Recent progress in the treatment of cancer in children. (1st April 2021) - Butler, Erin; Ludwig, Kathleen; Pacenta, Holly L.; Klesse, Laura J.; Watt, Tanya C.; Laetsch, Theodore W.
Abstract: Although significant improvements have been made in the outcomes of children with cancer, the pace of improvement has slowed in recent years as the limits of therapy intensification may have been reached for many pediatric cancers. Furthermore, with increasing numbers of pediatric cancer survivors, the long‐term side effects of treatment have become increasingly apparent. Therefore, attention has shifted to the use of molecularly targeted agents and immunotherapies to improve the outcomes of children who are not cured by traditional cytotoxic chemotherapies and to decrease exposure to cytotoxic chemotherapy and reduce late effects. This review describes the recent progress in the treatment of children with cancer, focusing in particular on diseases in which targeted and immunotherapeutic agents have made an impact.